Automotive NVH Technology - Fuchs, Anton; Nijman, Eugenius; Priebsch, Hans-Herwig.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents seven chapters examining selected noise, vibration and harshness (NVH) topics that are highly relevant for automotive vehicle development. These include applications following the major trends toward increased passenger comfort, vehicle electrification and lightweight design. The authors of the seven chapters, all of which are experts from the automotive industry and academia, present the foremost challenges and potential solutions in this demanding field. Among others, applications for sound optimization in downsized engines, noise optimization in electric powertrains, weight reduction options for exhaust systems, porous materials description, and the vibro-acoustic analysis of geared systems are discussed.
Sound optimization for downsized engines -- Assessment of the vehicle's interior wind noise due to measurement of exterior flow quantities -- Numerical investigation of location and coherence of broadband noise sources for a low speed axial HVAC fan -- Possibilities an constraints for lightweight in exhaust systems -- Noise optimization of an e-powertrain in a Pan-European EV project -- Synchronization of source signals for transfer path analysis and synthesis -- Modeling of gearbox whining noise -- Patch transfer function approach for analysis of coupled vibro-acoustic problems involving porous materials -- Near field acoustical holography for the characterization of cylindrical sources -- A combined computational-experimental approach for modeling of coupled vibro-acoustic problems.
Keywords: Automotive engineering; Acoustics; Transportation engineering; Traffic engineering; Automotive Engineering; Acoustics; Transportation Technology and Traffic Engineering